2009
DOI: 10.1182/blood-2008-10-183525
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 transactivator protein induction of suppressor of cytokine signaling-2 contributes to dysregulation of IFNγ signaling

Abstract: IntroductionAIDS is characterized by a profound reduction of CD4 ϩ T lymphocytes, immune defects, and cytokine dysregulation, leading to opportunistic infections and tumorgenesis. 1 HIV-1 has been identified to be the primary etiologic agent. Among HIV-1 gene products, transactivator protein (Tat) is required for efficient viral gene expression by interacting with the HIV long terminal repeat to enhance transcription and RNA processing. 2 Apart from its effects on viral replication, Tat is secreted extracellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 50 publications
1
31
0
Order By: Relevance
“…Furthermore, HIV-1 Tat-induced SOCS2 has also been reported to inhibit IFN-␥ signaling in monocytes (10). Cheng et al recently showed that HIV-1 Tat is sufficient to dampen both STAT1 activation and downstream target gene expression in response to IFN-␥ but that this protective immune response is restored following knockdown of SOCS2 (10). Although the authors of this study did not evaluate the effect of Tat-induced SOCS2 on pathogen clearance, these data suggest that multiple HIV-1-induced SOCS proteins may promote secondary infections by inhibiting the antipathogenic effects of IFN-␥.…”
Section: Effects Of Socs Expression On Viral Diseasementioning
confidence: 67%
See 1 more Smart Citation
“…Furthermore, HIV-1 Tat-induced SOCS2 has also been reported to inhibit IFN-␥ signaling in monocytes (10). Cheng et al recently showed that HIV-1 Tat is sufficient to dampen both STAT1 activation and downstream target gene expression in response to IFN-␥ but that this protective immune response is restored following knockdown of SOCS2 (10). Although the authors of this study did not evaluate the effect of Tat-induced SOCS2 on pathogen clearance, these data suggest that multiple HIV-1-induced SOCS proteins may promote secondary infections by inhibiting the antipathogenic effects of IFN-␥.…”
Section: Effects Of Socs Expression On Viral Diseasementioning
confidence: 67%
“…These studies suggest that HIV-1 Tat-induced SOCS3 disrupts protective type I IFN signaling within macrophages, allowing for enhanced viral replication and viral pathogenesis. HIV-1 Tat has also been shown to attenuate type II IFN signaling in human monocytes in a SOCS2-dependent manner (10). This finding has significant implications for protection from bacte- VOL.…”
Section: Virally Exploited Functions Of Socs Proteinsmentioning
confidence: 99%
“…Treatment of cells with recombinant Tat has been suggested to suppress IFNγ signaling through upregulation of SOCS2 [63] and Tat has been reported to interact with PKR, modulating its function [64]. Expression of Tat in dendritic cells leads to induction of interferon-inducible genes encoding T cell chemo-attractants, luring these target cells to sites of infection [36].…”
Section: Discussionmentioning
confidence: 99%
“…Socs1 and Socs3 also have the additional kinase inhibitory region (KIR) and extended SH2 motif (ESS) upstream of SH2 domain, which are absent in other SOCS members (Piessevaux et al 2008b). SOCS proteins are widely expressed at tissue level (Delgado-Ortega et al 2011), and their production can be induced by microbial/ viral infection or by cytokine treatment (Hebenstreit et al 2003, Cheng et al 2009). At cellular level, SOCS expression is well documented to serve as the feedback repressor for cytokine signaling via inhibition of JAK/ STAT pathway (Croker et al 2008) and plays a protective role in preventing hyperactivation of immune system, which can lead to autoimmune/inflammatory disorders (Liang et al 2014).…”
Section: Introductionmentioning
confidence: 99%